1999
DOI: 10.1095/biolreprod60.5.1263
|View full text |Cite
|
Sign up to set email alerts
|

Defects in the Germ Line and Gonads of Mice Lacking Connexin431

Abstract: The connexins are a family of at least 15 proteins that form the intercellular membrane channels of gap junctions. Numerous connexins, including connexin43 (Cx43), have been implicated in reproductive processes by virtue of their expression in adult gonads. In the present study, we examined the gonads of fetal and neonatal mice homozygous for a null mutation in the Gja1 gene encoding Cx43 to determine whether the absence of this connexin has any consequences for gonadal development. We found that in both sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
202
1
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(221 citation statements)
references
References 44 publications
11
202
1
7
Order By: Relevance
“…The presence of Cx43 gap junctions has been demonstrated by Aravindakshan and Cyr [49] to be essential for cellular communication between Sertoli cells. Cellular coordination, which is mediated by gap junctions, is crucial for the development and function of reproductive tissues [50]. It is therefore significant that these key interactions are reduced or disappear following exposure to TBT.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Cx43 gap junctions has been demonstrated by Aravindakshan and Cyr [49] to be essential for cellular communication between Sertoli cells. Cellular coordination, which is mediated by gap junctions, is crucial for the development and function of reproductive tissues [50]. It is therefore significant that these key interactions are reduced or disappear following exposure to TBT.…”
Section: Discussionmentioning
confidence: 99%
“…Adherens junctions are also present in the hematopoietic niche, where they anchor the HSC to the osteoblasts via N-cadherin and ␤-catenin . Gap junctions, formed by connexins and responsible for chemical and electrophysiological communication between adjacent cells, play a role in the spermatogonial niches as revealed by germ cell defects in Cx 43 Ϫ/Ϫ mice, but not in Cx 32 or Cx 40 knock-in mice (Juneja et al, 1999;Plum et al, 2000).…”
Section: Signaling In Adult Neural and Other Stem Cell Nichesmentioning
confidence: 99%
“…Soluble factors such as BMPs (Xie and Spradling, 1998;Kobielak et al, 2003;Zhang et al, 2003;Andl et al, 2004;He et al, 2004;Yamashita et al, 2005), FGFs (Kashiwakura and Takahashi, 2005), Shh (Madison et al, 2005;Crosnier et al, 2006), and Wnts (Gat et al, 1998;Korinek et al, 1998;Huelsken et al, 2001;Niemann et al, 2002;Reya et al, 2003;Willert et al, 2003) are present within the niche and can originate from support cells, stem cells themselves, or differentiated cell. Cell-to-cell contact-mediated signaling is also present in adult niches in the form of connexins (Juneja et al, 1999;Plum et al, 2000), ephrins/eph (Batlle et al, 2002;Holmberg et al, 2006) and Notch (Harada et al, 1999;Lowell et al, 2000;Conboy and Rando, 2002;Calvi et al, 2003;Conboy et al, 2003;Kumano et al, 2003;Tummers and Thesleff, 2003;Hadland et al, 2004;Fre et al, 2005;Robert-Moreno et al, 2005;van Es et al, 2005;Spradling, 2006, 2007;Song et al, 2007). These signaling mechanisms may occur between stem cells, between support cells and stem cells, and between stem cells and differentiating cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that alterations in spermatogenesis, in both human (Steger et al, 1999) and mouse (Batias et al, 1999), are associated with decreased Cx43 expression in adult Sertoli cells. In addition, the number of germinal cells in fetal testis from Cx43 knock-out mice is significantly reduced (Juneja et al, 1999). Moreover, substitution of the coding region of the Cx43 gene by coding sequences of Cx40 or Cx32 is not sufficient to prevent reduction in germinal cells, and still results in infertile males due to the complete absence of secondary spermatogonia (Plum et al, 2000).…”
mentioning
confidence: 99%